Mechanism of DMOC in Diabetes Mellitus with Liver Fibrosis - Zizhi XIAO; Hong SHI; Huanwen RAO; Lifen LUO (康复学报)
Objective:To establish a rat model of high-fat and high-sugar diet combined Streptozotocin(STZ)to explore the anti-oxidative, anti-inflammatory and anti-fibrotic mechanisms of the dendrobium mixture in order cycle method(DMOC)in diabetes mellitus with liver fibrosis.Methods:Forty healthy and clean male Sprague Dawley rats at five weeks of age were randomly divided into the control group(n=10, basic diet), the control intervention group(n=10, basic diet and DMOC), the model group(n=10, high fat and high glucose combined STZ)and the model intervention group(n=10, high fat and high glucose, STZ combined DMOC)after one week of adaptive feeding. The rats in each group were fed their corresponding diet and given reverse osmosis water to drink. The rats were weighed once a week and the feeding amount was adjusted according to body weight. The control group and the control intervention group were fed a basic diet, and the model group and the model intervention group were fed a high-fat and high-sugar diet for four weeks and then received two injections of STZ(the surface area of the body weight was calculated to be 25 mg, 72 h apart).Four days later, fasting blood glucose levels were≥11.1 mmol/L(screened by the glucometer), making this a successful diabetic rat model. Liver biopsy at the 36th week showed a tendency of liver fibrosis in the model group and the model intervention group. DMOC intervention was conducted in the control group and the control intervention group at the 36th-44th week and animal samples were taken in all groups at the 44th week. DCFH-DA assay was used to detect ROS content in rat blood;ELISA was used to detect TNF-α, IL-6, and TGF-β1 content in rat blood;Masson's trichrome stain method was used to observe the changes of fibrosis in liver tissue;immunohistochemical method was used to observe the changes of Fibronectin and IV-Collagen in liver tissue;Western Blot was used to observe protein expression of Smad2, Smad3, pSmad2, pSmad3, α-SMA, MMP1, MMP2 and MMP9 in liver tissue.Results:Testing changes of anti-oxidation, anti-inflammation and anti-liver fibrosis in blood: the content of ROS, TNF-α, IL-6 and TGF-β1 in the model intervention group were significantly lower than those in the model group(P<0.01).Observe the changes of fibrosis in liver tissue: liver tissue was found along the area around the portal vein with obvious hepatocyte necrosis and infiltration of inflammatory cells. Detection of Fibronectin and IV-Collagen in liver tissue: the Fibronectin and IV-Collagen fibers caused by liver tissue were distributed along the sediments, the presence and content of Fibronectin and IV-Collagen were significantly increased. Protein expression changes of Smad2, Smad3, α-SMA, MMP1, MMP2 and MMP9 in liver tissue: compared with the model group, the relative density of pSmad2/Smad2, pSmad3/Smad3 and α-SMA/β-actin in the model intervention group were decreased significantly(P<0.01), and the relative density of MMP1/β-actin, MMP2/β-actin and MMP9/β-actin were increased significantly(P<0.01).Conclusion:DMOC can reduce the accumulation of collagen fibers such as Fibronectin and IV-Collagen in diabetes mellitus with liver fibrosis. The DMOC mechanism in diabetic rats with liver fibrosis may be related to the inhibition effect of DMOC on ROS, TNF-α and IL-6.DMOC could promote the degradation of Fibronectin and IV-Collagen by down-regulating the protein expression of Smad2, Smad3 and α-SMA, and up-regulating the protein expression of MMP1, MMP2 and MMP9.